2019
DOI: 10.3389/fimmu.2019.01752
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-inflammatory Compound Candesartan Cilexetil Improves Neurological Outcomes in a Mouse Model of Neonatal Hypoxia

Abstract: Recent studies suggest that mild hypoxia-induced neonatal seizures can trigger an acute neuroinflammatory response leading to long-lasting changes in brain excitability along with associated cognitive and behavioral deficits. The cellular elements and signaling pathways underlying neuroinflammation in this setting remain incompletely understood but could yield novel therapeutic targets. Here we show that brief global hypoxia-induced neonatal seizures in mice result in transient cytokine production, a selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 65 publications
4
27
0
Order By: Relevance
“…This data showed that TLR2 plays a role in initiating inflammation after perinatal brain injury [ 85 , 86 ]. Supporting this data, the use of Candesartan Cilexetil, a drug which reduces levels of TLR2, has been shown to improve neuronal damage after hypoxia in mice, and also improve the long-lasting neurological outcomes [ 11 ]. Importantly, the response of TLR2 to sterile (e.g., HI) or non-sterile inflammation (e.g., LPS to mimic bacterial infection) differs on the pre-clinical model [ 84 ].…”
Section: Inflammation In Neonatal Encephalopathymentioning
confidence: 95%
See 3 more Smart Citations
“…This data showed that TLR2 plays a role in initiating inflammation after perinatal brain injury [ 85 , 86 ]. Supporting this data, the use of Candesartan Cilexetil, a drug which reduces levels of TLR2, has been shown to improve neuronal damage after hypoxia in mice, and also improve the long-lasting neurological outcomes [ 11 ]. Importantly, the response of TLR2 to sterile (e.g., HI) or non-sterile inflammation (e.g., LPS to mimic bacterial infection) differs on the pre-clinical model [ 84 ].…”
Section: Inflammation In Neonatal Encephalopathymentioning
confidence: 95%
“…The role of inflammation in neonatal seizures is not fully understood. We know that targeting inflammation before hypoxia reduced the number of seizure events and the duration of seizures [ 10 , 11 ]. The mechanism by which this targeting of inflammation reduces seizure activity will require further investigation.…”
Section: Neonatal Encephalopathy and Neonatal Seizuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Purinergic signalling is involved in many processes known to contribute to epileptogenesis and to potentiate damage. Targeting inflammation following neonatal seizures, a process in which purinergic signalling is heavily involved, has shown promise to reduce the development of epilepsy and behavioural deficits [302].…”
Section: Potential Purinergic Targets To Explorementioning
confidence: 99%